Reliability and validity of a novel Haemophilia‐specific Self‐Efficacy Scale. (11th April 2014) - Lock, J.; Raat, H.; Peters, M.; Tamminga, R. Y. J.; Leebeek, F. W. G.; Moll, H. A.; Cnossen, M. H.
Summary: Higher self‐efficacy in chronic disease patients is associated with higher development of self‐management skills and increased quality‐of‐life. Quantification and monitoring of self‐efficacy is therefore of importance. Self‐efficacy in haemophilia patients has received little attention due to lack of standardized scales. To validate the novel Haemophilia‐specific Self‐Efficacy Scale (HSES) in haemophilia patients on prophylactic home treatment, haemophilia patients aged 1–18 years on prophylactic treatment ≥1 year were included from three Dutch Haemophilia Treatment Centres. The HSES consists of 12 items, relating to perceptions of the ability to function on a day‐to‐day basis with regard to patient's disease. Retest was performed in a subsample. Validity was proven by the General Self‐Efficacy Scale and by the health‐related quality‐of‐life assessment tool Haemo‐QoL. Data were analysed from 53 children (response 75%), with a mean age of 9.8 years (SD 4.0). Mean total scale score of HSES was 55.5 (SD 4.7; range 38–60), with a ceiling effect of 17%. The HSES showed adequate internal consistency (Cronbach's alpha 0.72) and good test – retest reliability (Intra‐Class‐Correlation coefficient 0.75; P < 0.01; n = 37). The c onvergent validity was adequate as haemophilia‐specific self‐efficacy correlated significantly with general self‐efficacy ( r = 0.38; P < 0.01). High HSES scores correlated significantly with quality‐of‐life as measured by the Haemo‐QoL ( r = −0.42; P ≤ 0.01). The novel HSES is a reliable and valid tool to assess self‐efficacy in paediatric haemophilia patients on prophylactic home treatment. High self‐efficacy correlated with higher quality‐of‐life, further underlining the importance to standardly assess, monitor and improve self‐efficacy.